North American Deglacial Marine- and Lake-Limit Surfaces - Dyke, Arthur; Dredge, Lynda; Hodgson, Douglas (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe deglacial marine-limit surface is a virtual topography that shows the increase of elevation since deglaciation. The currently available set of marine-limit elevations (n = 929), about three times the number available in the most recent synthesis, allows a fairly detailed rendering of the surface across most of glaciated North America and Greenland. Certain large glacial lake-limit surfaces are analogous to marine-limit surfaces, except that their gradients were not dampened by eustatic sea-level rise. Collectively the surfaces reflect both gross ice-sheet geometry and regional to local rates of ice-marginal recession. As such, they are replication targets for glacioisostatic modelling that are supplementary to and more continuously distributed than relative sea-level curves.